Accounting Information Systems Design of Budget Realization Audit through ACL from SAIBA application: Case Study on Public University - Ismanu, Sidik; Putri, Diana Rino; Haris, Zainal Abdul (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
The purpose of this research is to provide an overview of the systems and procedures for audit process flow of Budget Realization Report through ACL (Case Study on Public University). This research was a qualitative study to describe the business flow by accounting information system design using Business Process Model and Notation (BPMN). Applied research is the method that used in this research. The type of research is R&D/Research and Development. This study uses secondary data sources from financial databases. Documentation is the method of data collection used in this research. The results of this study is to propose systems and procedures for audit process flow of Budget Realization Report through Audit Command Language (ACL). Previously, auditing financial statements was still applied manually. Therefore, the result of the business process model of budget realization audit in this research is already computer based. With the benefits of applying computer-assisted audit techniques, auditors are helped because the work can be done more effectively and efficiently.